The role of a media arts gallery in a polytechnic university to enhance entrepreneurship - Brigas, Joaquim; Gonçalves, Fátima; Marques, Henrique; Gonçalves, Jorge (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This paper explores the role of a media art gallery within a university setting. Specifically, it examines how mahaus.gallery can contribute to the intellectual and cultural life of the university community. The paper discusses the ways in which a media art gallery can promote interdisciplinary learning and research, foster creative collaborations, and engage with the wider community beyond the university campus. Therefore, through a quantitative approach, we analyzed the role of a media arts gallery in a higher education institution in stimulating entrepreneurship among communication students. The results highlight the importance of interdisciplinary collaboration and institutional support in the development of entrepreneurial skills and indicate that mahaus.gallery is an essential component of the university as it provides a space for innovation, experimentation and critical reflection on the intersection of art and technology.